Balikpapan City Development: Key Sectors for Sustainable Growth - Grace Natalia Marpaung; Medi Elfiani; Annis Nurfitriana Nihayah; Dwi Rahmayani; Tutik (Economics Development Analysis Journal, 2024)
The main challenge faced by the City of Balikpapan is the disparity in facilities between sub-districts and the lack of optimal development of leading sectors that have the potential to support sustainable economic growth. Inequality in public facilities causes access to essential services, such as education, health, and the economy, to be unequal across city areas. This research aims to identify leading sectors in Balikpapan City and formulate development strategies focusing on sustainable economic growth, equitable distribution of public facilities, and strategic investment recommendations. The research uses quantitative descriptive methods with secondary data from the Central Statistics Agency (BPS) and related literature and analysis of Location Quotient (LQ), Shift Share, Klassen Typology, and Scalogram for the 2016-2022 period. The research results show that the processing industry, electricity and gas supply, and construction sectors are leading sectors with high competitiveness. However, there are disparities in public facilities, especially in North Balikpapan, which has more complete facilities than other sub-districts. These findings indicate the need for a development strategy that prioritizes the development of leading sectors, improving infrastructure, and increasing investment to achieve sustainable economic growth and a better quality of life for the community. The development strategy must focus on equal distribution of public facilities and strengthening leading sectors to make Balikpapan a more livable and economically competitive city